PEMBINAAN BUDIDAYA IKAN LELE BERBASIS TEKNOLOGI REKAYASA HORMONAL PADA PETERNAK LELE TW BATAM KEPULAUAN RIAU - Delia Meldra Meldra; Albertus L. Setyabudhi; Yopy Mardiansyah (Jurnal Tiyasadarma, 2023)
The increasing market demand for catfish commodities in Batam city should stimulate the catfish farming business to be more advanced, but there are obstacles faced by small farmers, namely poor seed quality, cannibalism and lack of additional knowledge to raise catfish with hormonal engineering technology. The purpose of this activity is to provide additional knowledge of hormonal recaysa technology, catfish sorting techniques, and minimize cannibalism. This activity was carried out at one catfish farmer in Temiang, namely TW, with each having two workers. The method used is to apply hormonal engineering technology for the spawning process and maintenance of catfish breeds, as well as fish pond captivity. The result is that catfish mothers are given ovaprim hormone injections, and spawning is carried out with a time difference for each brood. After the spawning process and producing catfish seeds, the maintenance process is carried out according to the spawning time and given feed that is pellets watered with a mixture of chicken skin cooking water and rGH hormones. From this treatment results in uniform catfish size according to spawning time and pond grouping reduces the rate of cannibalism. The level of achievement of activities is very good, where each stage produces good output. This activity produces good quality germ with the help of ovaprim hormone, pond captivity with the aim of each size is facilitated, fry are given the addition of rGH growth hormone in pellets so that catfish have size uniformity so that cannibalism is reduced.